PENGARUH MENDENGARKAN AYAT SUCI AL QURAN TERHADAP TINGKAT KECEMASAN PASIEN SEBELUM TINDAKAN EKSTRAKSI GIGI - Syafrudin Aulia Azhar; Rahmawati Sri Praptiningsih; Erna Dwi Agustin (Faculty of Dentistry, Universitas Islam Sultan Agung, 2016)
Background: Anxiety is a normal reaction is for the individual against a very pressing situation. Individuals who experience anxiety when visiting the dentist called Dental Anxiety. Dental anxiety due to bad experiences in previous treatments. Physiological signs of anxiety is increased pulse rate. Listening to the Quran can provide a relaxing effect so it can reduce anxiety. The purpose of this study to determine the effect of listening to the Koran on the anxiety level of the patient before tooth extraction.Method: Quasi experiment study with pre-posttest with control group design was conducted on 38 extraction patient and divided into two groups: a control group that did not listen to the Quran and the treatment group who listened to the Quran before extraction. The pulse rate of control groups were measured at the time when patients came in and 5 minutes later. The pulse ate of treatment group were measured at the time when patients came in and after the patient were listened to Quran. Data were analyzed by Independent T-Test .Result: The result showed the average pulse rate in the treatment group before and after were 67.26 and 62.68, while the average pulse rate in the control group before and after were 65.89 and 65.84. Independent T-test results showed p=0.000, it's mean that there are significant differences of the pulse rate between the treatment group and the control group on the anxiety level of the patient before tooth extraction.Conclusion: It can be concluded that listening to the Quran could reduce patient anxiety before dental extraction.